Research of alternative feedstock application ways for pyrolysis; Recent Achievements and Prospects of Innovations and Technologies; Iss. 3 : Proceedings of the XIII All-Russian Research-to-Practice Conference of Students, Postgraduates and Young Scientists, Kerch, April 22, 2024 - Alina A. V. Anna Vladimirovna (2024, 2024)
This article discusses the process of pyrolysis, specifically exploring the possibilities of using alternative types of feedstock for the pyrolysis process, with a main focus on the pyrolysis of rubber, plastics, and biomass. The efficiency and prospects of using different types of feedstock are studied, as well as potential benefits and limitations of this approach, offering promising solutions for waste disposal and increasing energy efficiency in production processes. The research results may be valuable for the development of more sustainable and efficient waste processing methods aimed at reducing the negative impact on the environment